DEVELOPMENT OF ISLAMIC ACTIVITY BASED ECONOMY - Afief, Muhammad (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2017)
Real Working Lecture (KKN) is subject intrakurikuler held by all colleges require students to interact with the community and the surrounding environment directly with the aim of increasing the capability and knowledge of students as a preparation to live in the community after graduation. KKN also a form of real devotion to the community college students, after getting the lecture material that can be useful in society itself. KKN implementation is expected to help the environment and improve human resources to people and students in the use and management of available resources. Independent KKN students to empower the villagers and village Mekarjaya Kabandungan by directing and driving force to always do the activities of Islamic economics in terms of both worship and mu'amalah. Development of Shariah-based economic activity is also seen the potential of available resources both human and natural resources. Human resources mobilized and directed to be more motivated to do things, which is based on sharia and natural resources processed and developed in order to provide benefit in the form of an increase in economic terms. Thus, the activities undertaken by the community will always be targeted and based on sharia in terms of both physical and non-physical.